The last house guest [compact disc, unabridged] : a novel - Miranda, Megan (Simon & Schuster Audio/Audioworks, 2019)
Littleport, Maine, has always felt like two separate towns: an ideal vacation enclave for the wealthy, and a simple harbor community for the year-round residents. Typically, fierce friendships never develop between a local and a summer girl, but that is just what happens with visitor Sadie Loman and local Avery Greer. Each summer for almost a decade, the girls are inseparable, until Sadie is found dead. While the police rule the death a suicide, Avery cannot help but feel there are those in the community who blame her, and she is intent on clearing her name before the facts are twisted against her.